(untitled) (Albayan Scientific Journal, 2023)
Diabetic kidney disease (DKD) is one of the most dangerous complications of Diabetes Mellitus type 2. the diabetes is affecting in many organs in the body especially the kidneys. KD results in increased hospitalizations and mortality rates, in particular due to cardiovascular complications, in addition to the growing difficulty of ambulatory treatment for patients with DM. The need for renal replacement therapies such as dialysis and kidney transplants also rise with DKD. there are many causes of kidney disease, but the diabetes may play a major role in kidney failure, for this reason we investigated and collected statistics from the Tobruk Medical Center in the kidney department trying to understand the relations between diabetes and renal disease whereas found in Tobruk Medical Centre about 100 (46 Females, 54 Males ) patients have renal dialysis, 57 who have DKD. kidney disease patients were older. According to this study, there is a relation between diabetes and kidney disease at Tobruk Medical Centre, and diabetes may lead to kidney failure and dialysis. Further studies are required to confirm these findings.